Factors Related to Nutritional Status of School-Age Cerebral Palsy Children - Yunita, Melin Fitri; Mardiana, Mardiana (Sport and Nutrition Journal, 2024)
Introduction: Cerebral palsy (CP) is one of the most common causes of chronic disability in children, nutritional disorders in children with CP can manifest as malnutrition or more nutrition. The percentage of CP in children under 18 years is 65.4% of the total CP people in Indonesia. Methods: The type of research is observational with a cross-sectional research design. Samples of 45 school-age school-age children who meet the criteria with total sampling. The instruments used are a 24-hour recall form, a food photo book, and a parenting questionnaire. Bivariate analysis in this study uses a chi-square test to determine the relationship between food intake and parenting with the nutritional status of CP children. Results: The results of the study are the relationship between energy intake and the nutritional status of CP children with the value of P=0.003. There is no relationship between protein intake and the nutritional status of CP children with the value of P=0,462. There is no relationship between parenting with the nutritional status of CP children, the value of P=0.97. There is a relationship between food consistency and the nutritional status of CP children obtained with the value of P=0.017.